Analysis of MyPertamina Application User Satisfaction Using End User Computing Satisfaction Method - Annisa Uswatun Hasanah; Bayu Waspodo; Elsy Rahajeng (APTIKOM SUMSEL, 2023)
The MyPertamina application is an application that functions as a cashless payment system, where this application can make it easier for users to make BBM payments. This study aims to determine the level of user satisfaction and the factors that influence their satisfaction with the MyPertamina application using the End User Computing Satisfaction (EUCS) approach. Since 2017 this application has been running, until now it is known that the number of existing MyPertamina users is still relatively low and far from the maximum potential of the vehicle population in Indonesia. Where MyPertamina users currently are approximately 5 million users, while the number of vehicles in Indonesia itself is currently 144 million units of vehicles. This causes the target user has not been achieved in accordance with what is expected by PT. Pertamina. It can be concluded that of the 5 hypotheses tested, 1 of them was rejected. So the factors that canaffect MyPertamina user satisfaction in terms of Content, Accuracy, Ease of Use, and Timeliness. Meanwhile, the format variable has no effect on MyPertamina user satisfaction.